2010
DOI: 10.1128/iai.00217-10
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with the Haemophilus ducreyi Hemoglobin Receptor HgbA with Adjuvant Monophosphoryl Lipid A Protects Swine from a Homologous but Not a Heterologous Challenge

Abstract: Haemophilus ducreyi, the etiological agent of chancroid, has a strict requirement for heme, which it acquires from its only natural host, humans. Previously, we showed that a vaccine preparation containing the native hemoglobin receptor HgbA purified from H. ducreyi class I strain 35000HP (nHgbA I ) and administered with Freund's adjuvant provided complete protection against a homologous challenge. In the current study, we investigated whether nHgbA I dispensed with monophosphoryl lipid A (MPL), an adjuvant ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 64 publications
1
38
0
Order By: Relevance
“…For example, immunoproteomic analysis of the whole cell proteins of Riemerella antipestifer revealed that TonB-dependent receptor was among the immunogenic outer membrane proteins (Q. , and a study with a Znuptake Tdr, ZnuD, of Neisseria meningitidis showed that it could induce bactericidal antibodies upon immunization of mice (Stork et al 2010). Similarly, Tdr with vaccine potentials have been found in Haemophilus ducreyi and, as reported by us, P. fluorescens (Afonina et al 2006, Fusco et al 2010, Leduc et al 2011, Y. Hu et al 2012. In this study, we found that, when used as subunit vaccines, the recombinant proteins rTdr1, rTdr2, and rTdr3 elicited moderate but significant protections that differed in magnitude, with the highest RPS being effected by rTdr3.…”
Section: Discussionmentioning
confidence: 84%
“…For example, immunoproteomic analysis of the whole cell proteins of Riemerella antipestifer revealed that TonB-dependent receptor was among the immunogenic outer membrane proteins (Q. , and a study with a Znuptake Tdr, ZnuD, of Neisseria meningitidis showed that it could induce bactericidal antibodies upon immunization of mice (Stork et al 2010). Similarly, Tdr with vaccine potentials have been found in Haemophilus ducreyi and, as reported by us, P. fluorescens (Afonina et al 2006, Fusco et al 2010, Leduc et al 2011, Y. Hu et al 2012. In this study, we found that, when used as subunit vaccines, the recombinant proteins rTdr1, rTdr2, and rTdr3 elicited moderate but significant protections that differed in magnitude, with the highest RPS being effected by rTdr3.…”
Section: Discussionmentioning
confidence: 84%
“…For example, a monovalent HgbA vaccine has shown promise in a pig model, where immunization with class I HgbA (HgbA I ) and Freund's adjuvant provided protection against a challenge with class I strains (1). However, immunization with HgbA I and monophosphoryl lipid A, an adjuvant approved for use in humans, resulted in protection against class I strains but not class II strains (13). This is not surprising, given the differences in the HgbA sequences in class I and II strains (45).…”
Section: Discussionmentioning
confidence: 93%
“…H. ducreyi strain 35000HP is the human-passaged variant (4) of wild-type isolate 35000 (14) and the prototypical strain for H. ducreyi class I strains (48). Strain FX547 is an isogenic hgbA deletion mutant of strain 35000HP (26), and FX548, an isogenic 35000HP strain in which the hgbA gene was replaced with hgbA of strain DMC111, a class II H. ducreyi strain (13). In this report, H. ducreyi strains 35000HP, FX547, and FX548 are designated 35000HPhgbA I , 35000HP⌬hgbA, and 35000HPhgbA II , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that active immunization with a native preparation of HgbA purified from H. ducreyi prototypical class I strain 35000HP (nHgbA I ) protects against a homologous challenge in the experimental swine model of chancroid (1,13). Protection was observed when using either Freund's adjuvant or an adjuvant approved for use in humans, monophosphoryl lipid A (MPL).…”
mentioning
confidence: 99%